Challenges and Advances in Chronic Low Back Pain Management: A Review of Conventional and Innovative Treatment Strategies - Cardozo-Batista, Leandro; Beltrame, Felipe Coelho; Sousa, José Carlos Gomes de; Moraes, Adriana Silva de; Silva, Sarah Camila Santos da; Biz, Giovanna; Nunes, Huendel Batista de Figueiredo; Hernandes, Linccon Fricks; Silva, Carlos Augusto de Souza; Carvalho, Sílvia Alves da Silva; Previato, Soraia; Sousa Neto, Carlos Humberto de; et al. (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: Chronic low back pain (CLBP) is a prevalent condition with complex management needs, requiring a multifaceted therapeutic approach. Objective: This study aimed to analyze the effectiveness of pharmacological, non-pharmacological, and innovative treatments for CLBP, highlighting multidisciplinary strategies and emerging therapies. Methods: A review of 11 studies published between 2020 and 2024 was conducted, focusing on treatment efficacy, patient outcomes, and the integration of various therapeutic modalities. Results: Multidisciplinary programs showed significant reductions in pain and disability demonstrating the benefits of comprehensive care. Non-pharmacological interventions, including manual therapy and acupuncture, provided sustained improvements in pain and function. Pharmacological treatments offered short-term relief but raised concerns about dependency risks, particularly with opioids like tramadol. Innovative therapies, such as spinal cord stimulation and regenerative treatments, presented promising results for patients unresponsive to conventional methods. Conclusion: Effective CLBP management requires integrating pharmacological and non-pharmacological treatments within multidisciplinary programs. Emerging therapies further expand treatment options, though long-term studies are needed to establish their efficacy and safety. A holistic, patient-centered approach remains essential for optimizing outcomes in CLBP care.